EFFECTIVE TECHNOLOGIES OF REMOTE CLEANING OF HEAT EXCHANGERS (International journal of artificial intelligence, 2025)
Research works aimed at increasing the use and efficiency of collectors of flat solar water heaters in world renewable energy systems. Today, new methods to increase the efficiency of thermal energy generation are widely used by thermal power structures.The inner walls of boilers, steam boilers and heat exchanger pipes are exposed to salts in the water used over time. Several methods are used to clean the equipment. However, viewed from this perspective, the invention and development of an environmentally friendly, cost-effective, highly efficient method that does not affect metal is one of the top priorities.The article describes the types of dismantled and non-dismantled heat exchangers for cleaning and protection from pollution, as well as methods of cleaning heat exchangers, the degree of its pollution, construction, features of substances constituting the surface.